Mercury stable isotopes suggest reduced foraging depth in oxygen minimum zones for blue sharks. (August 2022) - Le Croizier, Gaël; Sonke, Jeroen E.; Lorrain, Anne; Serre, Sandrine; Besnard, Lucien; Schaal, Gauthier; Amezcua-Martinez, Felipe; Point, David
Abstract: Oxygen minimum zones (OMZs) are currently expanding across the global ocean due to climate change, leading to a compression of usable habitat for several marine species. Mercury stable isotope compositions provide a spatially and temporally integrated view of marine predator foraging habitat and its variability with environmental conditions. Here, we analyzed mercury isotopes in blue sharks Prionace glauca from normoxic waters in the northeastern Atlantic and from the world's largest and shallowest OMZ, located in the northeastern Pacific (NEP). Blue sharks from the NEP OMZ area showed higher Δ 199 Hg values compared to sharks from the northeastern Atlantic, indicating a reduction in foraging depth of approximately 200 m. Our study suggests for the first time that blue shark feeding depth is altered by expanding OMZs and illustrates the use of mercury isotopes to assess the impacts of ocean deoxygenation on the vertical foraging habitat of pelagic predators. Graphical abstract: Unlabelled Image Highlights: Hg isotope compositions in blue sharks from an OMZ area and normoxic conditions Higher Δ 199 Hg values in sharks from the OMZ suggest reduced feeding depth. Ocean deoxygenation alters the vertical foraging habitat of pelagic predators.